1988
DOI: 10.1099/0022-1317-69-6-1285
|View full text |Cite
|
Sign up to set email alerts
|

Physical Maps and Comparative DNA Hybridization of Mamestra Brassicae and Panolis Flammea Nuclear Polyhedrosis Virus Genomes

Abstract: SUMMARYThe genome DNAs from the Panolis flammea (Pf) multiple nucleocapsid nuclear polyhedrosis virus (MNPV) and the Mamestra brassicae (Mb) MNPV were analysed with the restriction endonucleases BamHI, BgllI, KpnI, HindlII, Sinai and XhoI. The profiles produced by each enzyme for the two virus genomes were quite dissimilar with very few comigrating fragments. The size of PfMNPV DNA was calculated to be 145 kilobase pairs (kbp) and that of MbMNPV 150 kbp. Physical maps of the two genomes were constructed utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 22 publications
3
36
0
Order By: Relevance
“…DNA restriction enzyme analysis and hybridization experiments have shown genetic relatedness between baculoviruses (Knudson & Tinsley, 1978;Smith & Summers, 1978Jewell & Miller, 1980;Vlak & Gr6ner, 1980;Harvey & Tanada, 1985;Rohrmann.et al, 1982;Wiegers & Vlak, 1984;Kislev, 1985;Possee & Kelly, 1988) and restriction endonuclease analysis of the viral genome has revealed that wild stocks of NPVs are often composed of several genetically different isolates (Lee & Miller, 1978;Miller & Dawes, 1978;Smith & Summers, 1978, 1979Miller et al, 1980;Knell & Summers, 1981 ;Gettig & McCarthy, 1982;Kislev & Edelman, 1982; t Present address: Odawara Research Institute, Nippon Soda Co. Ltd, Odawara 250-02, Japan.…”
Section: Introductionmentioning
confidence: 99%
“…DNA restriction enzyme analysis and hybridization experiments have shown genetic relatedness between baculoviruses (Knudson & Tinsley, 1978;Smith & Summers, 1978Jewell & Miller, 1980;Vlak & Gr6ner, 1980;Harvey & Tanada, 1985;Rohrmann.et al, 1982;Wiegers & Vlak, 1984;Kislev, 1985;Possee & Kelly, 1988) and restriction endonuclease analysis of the viral genome has revealed that wild stocks of NPVs are often composed of several genetically different isolates (Lee & Miller, 1978;Miller & Dawes, 1978;Smith & Summers, 1978, 1979Miller et al, 1980;Knell & Summers, 1981 ;Gettig & McCarthy, 1982;Kislev & Edelman, 1982; t Present address: Odawara Research Institute, Nippon Soda Co. Ltd, Odawara 250-02, Japan.…”
Section: Introductionmentioning
confidence: 99%
“…This virus was activated by feeding the M. brassicae larvae with either the closely related Panolis flammea multiple nucleocapsid nucleopolyhedrovirus (PaflMNPV), or the more distantly related Autographa californica (Ac) MNPV. DNA profiles from the activated virus showed that it was very closely related, if not identical, to M. brassicae (Mb) MNPV (Possee & Kelly, 1988). PCR amplification of polyhedrin gene sequences demonstrated that the MbMNPV-like virus was present in the egg, larval, pupal and adult stages of the insect life-cycle.…”
mentioning
confidence: 99%
“…It has been released in the UK on a large scale for the control of the pine beauty moth, Panolis flammea (Entwistle & Evans, 1987). However, the molecular biology of this virus is poorly understood and polyhedrin is the only MbMNPV gene sequenced to date (Possee & Kelly, 1988;Cameron & Possee, 1989). MbMNPV is therefore an attractive subject for both genetic analysis and recombinant studies with a view to future field studies.…”
mentioning
confidence: 99%